2016
DOI: 10.22453/lsj-017.2.217232
|View full text |Cite
|
Sign up to set email alerts
|

DFT and QSAR study of corrosion inhibition on 3,5-di-substituted pyrazole derivatives with heteroatom on position one

Abstract: MTHT) were investigated at density functional theory (DFT) B3LYP/6-31G** (d,p) level. The calculated molecular descriptors such as the HOMO, LUMO, the dipole moment, chemical potential (μ), chemical hardness (ղ), softness (s), global nucleophilicity (N) and average Mulliken charges on nitrogen atoms are discussed in relation to the observed inhibitory efficiency for the compounds. The developed qualitative structural activity relationship (QSAR) models relate the calculated molecular descriptors to the corrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…While few studies have shown that low μ value do favour the adsorption of inhibitor molecules on the MS surface, thus increasing the inhibition effectiveness. Hitherto others have proposed an opposite correlation where high μ value enhances the NSAIDs adsorption on the MS surface, which in turns favor higher %IE …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…While few studies have shown that low μ value do favour the adsorption of inhibitor molecules on the MS surface, thus increasing the inhibition effectiveness. Hitherto others have proposed an opposite correlation where high μ value enhances the NSAIDs adsorption on the MS surface, which in turns favor higher %IE …”
Section: Resultsmentioning
confidence: 99%
“…ΔE (energy gap) between the LUMO and HOMO energy levels determine %IE. [15,[36][37][38][39] Studies have shown that the lower ΔE values indicate higher inhibitory effectiveness because the excitation energy gap is more favorable and is associated with chemical reactivity. [40] In our case, Aspirin has least ΔE value and highest E HOMO value thereby indicating it to exhibit greater inhibition efficiency which pronouns to be in good agreement with the experimental results ( Figure 12).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The optimized molecular structures of TZ CDI are shown in Figure 3. In general, the inhibition efficiency of an inhibitor is associated with its electronic structure [32], especially some calculated quantum chemical descriptors such as the E HOMO , the E LUMO , the ∆E gap , η, χ, and Fukui function. Table 3 shows the obtained values of these parameters for the studied inhibitor.…”
Section: Geometries and Global Reactivitymentioning
confidence: 99%